2000
DOI: 10.1046/j.1365-2222.2000.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to inhaled antigen by intratracheal instillation of dendritic cells

Abstract: Delivering antigen to the respiratory tract via professional antigen-presenting DCs sensitizes for a secondary response to inhaled antigen leading to airway inflammation. This model will prove very useful for studying the early events of sensitization to inhaled antigen using the respiratory route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 41 publications
3
50
0
Order By: Relevance
“…During the effector phase of the immune response, effector T cells are recruited into the lung and again stimulated by DCs to release cytokines and orchestrate airway inflammation (5,24). The occurrence and the nature of the secondary effector response reflects the character of the primary response and the development of polarized Th1 or Th2 responses during the central processing phase (25). Challenge with aerosolized OVA in mice that were immunized by intratracheal injection of OVA-DC, led to the accumulation of activated CD4 + T lymphocytes in the airways and to eosinophilic airway inflammation and goblet cell hyperplasia, both characteristic of allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…During the effector phase of the immune response, effector T cells are recruited into the lung and again stimulated by DCs to release cytokines and orchestrate airway inflammation (5,24). The occurrence and the nature of the secondary effector response reflects the character of the primary response and the development of polarized Th1 or Th2 responses during the central processing phase (25). Challenge with aerosolized OVA in mice that were immunized by intratracheal injection of OVA-DC, led to the accumulation of activated CD4 + T lymphocytes in the airways and to eosinophilic airway inflammation and goblet cell hyperplasia, both characteristic of allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used in vitro differentiated BMDCs of wild-type (WT), C3aR 2/2 , C5aR1 2/2 , or C3aR 2/2 /C5aR1 2/2 origin as a surrogate for pulmonary cDCs to evaluate the role of AT receptor signaling in cDCs for the development of HDM-induced allergic asthma. BMDCs have been frequently used in the past as a surrogate for pulmonary APCs to study the role of cDCs in asthma development (31)(32)(33)(34)(35). This study has been designed to provide new insights into the role of C3aR and C5aR1 signaling in cDCs on the development of AHR, airway inflammation, mucus production, as well as Th1, Th2, and Th17 cytokine production.…”
Section: /2mentioning
confidence: 99%
“…Asthma phenotype or control mice (n ϭ 5 per group) were surgically anesthetized with ketamine/xylazine, then the skin and musculature over their trachea were carefully reflected surgically, and 1 ϫ 10 5 dendritic cells in 25 l of saline were injected transtracheally using a 30-gauge needle. Dendritic cells given in this fashion have been shown by others to migrate across the airway epithelium, to the draining lymph nodes, where they efficiently present their Ags for sensitization of the treated animals (22)(23)(24). The cutaneous incisions in our animals were closed with surgical staples.…”
Section: Animal Sensitization and Challengementioning
confidence: 99%
“…Although we did not assess trafficking of our cells in vivo, others have shown that dendritic cells introduced into the airways traverse the airway-epithelial barrier, migrate to the draining lymph nodes, and there successfully present their Ags (e.g., Refs. [22][23][24]. This rapid phase of T cell activation is Ag-specific and does not occur in nondraining lymph nodes or the spleen, but the activated cells do recirculate to other secondary lymphoid organs after a moderate delay (23), and this recirculation leads to subsequent systemic sensitization (22).…”
Section: Figure 5 Cd8␣mentioning
confidence: 99%